A SYSTEMATIC APPROACH TO THE ANALYSIS AND ELIMINATION OF CONFLICTS IN SPECIAL PURPOSE WIRELESS NETWORKS - Pampukha, Igor; Skrypnichenko, Andrii (Science-based technologies, 2024)
The task of ensuring the end-to-end quality of service of heterogeneous wireless (WW) networks with random multiple access is considered. The processes of the occurrence of conflicts between the fairness and optimality of route selection and resource allocation in BP networks are analyzed. A technique for eliminating conflicts between fairness and optimality of resource distribution has been developed. It is shown that in the rational definition of radio access technology in heterogeneous networks, the functions of each level and, accordingly, the information parameters of the traffic at this level can be attributed to one of two alternative groups: functions that depend on a specific technical implementation of the network or functions oriented to work with applications. Accordingly, a global approach to the optimal selection of a radio access technology (RAT) is formulated as a problem with super-polynomial complexity, and an approach for RAT selection using a distributed metaheuristic tabu search algorithm based on the peak rate that users are able to perceive is proposed. A distributed RAT selection system based on metaheuristic optimization of the set of routes with elimination of redundancy has been developed. A combined metaheuristic optimization method based on a dual approach - a combination of adaptability and learning from previously obtained results - has been developed. An original method of one-time overcoming the prohibition of tabu search paths has been introduced: when the next step is considered unpromising and should be rejected, but good results were obtained from the previous steps - this step is allowed, and the obtained result is counted as an initial one for further search. A general expression for the distribution of the access point's stay time in a heterogeneous wireless network together with the access point boundary crossing probabilities is obtained. Numerical results and simulation results show satisfactory agreement.